RAFT copolymerization of alginate-derived macromonomers - synthesis of a well-defined poly(HEMAm)-graft-(1 4)-α-L-guluronan copolymer capable of ionotropic gelation - Rinaudo, Marguerite (2014)
The aqueous RAFT copolymerization of methacrylamide- and methacrylate-functionalized (1→4)-α-L-guluronan and (1→4)-β-D-mannuronan macromonomers with N-(2-hydroxyethyl)methacrylamide afforded synthetic-g-polysaccharide copolymers with a predetermined and well-defined molar mass (“grafting through” approach). One such polymer featuring guluronan graft chains of Xn = 21 was able to undergo ionotropic gelation in the presence of Ca2+ ions and to form a soft hydrogel in spite of the fairly low molar mass (Mn = 77 000 Da). The high yield synthesis of a new methacrylate-functionalized (1→4)-α-L-guluronan is also reported.